2020
DOI: 10.1128/jcm.01592-19
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Findings Are Poor Predictors of Appropriate FilmArray Meningitis/Encephalitis Panel Utilization in Pediatric Patients

Abstract: Molecular testing of cerebrospinal fluid (CSF) using the BioFire FilmArray meningitis/encephalitis (FA-M/E) panel permits rapid, simultaneous pathogen detection. Due to the broad spectrum of targeted organisms, FA-M/E testing may be restricted to patients with abnormal CSF findings. We sought to determine if restriction is appropriate in our previously healthy and/or immunocompromised pediatric patients. FA-M/E was ordered on 1,025 CSF samples from 948 patients; 121 (11.8%) specimens were FA-M/E positive. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
0
16
0
1
Order By: Relevance
“…Abnormal CSF parameters values for glucose, protein, and pleocytosis are often used as an indicator of CNS infection, but the utility of these parameters in pediatric setting has been dubious (12,35,36). In our study, we found that in majority of the cases of HHV-6 infection of the CNS occurred in the presence of normal CSF parameters.…”
Section: Discussionmentioning
confidence: 52%
“…Abnormal CSF parameters values for glucose, protein, and pleocytosis are often used as an indicator of CNS infection, but the utility of these parameters in pediatric setting has been dubious (12,35,36). In our study, we found that in majority of the cases of HHV-6 infection of the CNS occurred in the presence of normal CSF parameters.…”
Section: Discussionmentioning
confidence: 52%
“…A prior study already showed that restricting FilmArray ME panel orders based on pleocytosis or other CSF abnormalities can result in missed diagnosis opportunities. 16 In that study, nearly 20% of patients with no pleocytosis and normal CSF glucose and protein had positive result with FilmArray ME panel. The identification of an etiological agent brings relevant information to the physician, the patient, and the family and can contribute to avoid further unnecessary diagnostic tests and clarifying the cause of the symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…While it is true that there are cases of viral CNS infection with normal CSF, such as early stages of herpetic encephalitis, 35 , 36 , 37 and enterovirus meningitis in neonates, 38 , 39 these are rare and occur in precise clinical settings. 40 Considering the limitations of FA/ME for some microorganisms and its relatively high cost, defining diagnostic algorithms approaches to define the group of patients who can benefit the most from this test is an urgent need.…”
Section: Discussionmentioning
confidence: 99%